2003
DOI: 10.1038/sj.ijo.0802466
|View full text |Cite
|
Sign up to set email alerts
|

Within- and between-laboratory precision in the measurement of body volume using air displacement plethysmography and its effect on body composition assessment

Abstract: OBJECTIVE:To determine and compare the extent of within-and between-laboratory precision in body volume (BV) measurements using air displacement plethysmography (ADP), the BOD POD body composition system, and to interpret any such variability in terms of body composition estimates. DESIGN: Repeated test procedures of BV assessment using the BOD POD ADP were reproduced at two laboratories for the estimation of precision, both within and between laboratories. SUBJECTS: In total, 30 healthy adult volunteers, 14 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…In a similar study to the present, Collins et al (2004) found that the interdevice reliability between BP units in separate laboratories was acceptable. However, the study observed relatively large 95% limits of agreement (À3.7 to 2.5 %BF), indicating that practitioners should heed caution when using two different units.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…In a similar study to the present, Collins et al (2004) found that the interdevice reliability between BP units in separate laboratories was acceptable. However, the study observed relatively large 95% limits of agreement (À3.7 to 2.5 %BF), indicating that practitioners should heed caution when using two different units.…”
Section: Discussionsupporting
confidence: 61%
“…In the current study, we found that the agreement in measured TGV values between the two BP units (r 2 ¼ 0.98, Po0.001) was as good as the agreement in repeated measurements of TGV by a single BP (r 2 ¼ 0.95, Po0.001) (Collins & McCarthy, 2003). In order to make a direct comparison in interdevice reliability with that from Collins et al (2004), we reassessed interdevice reliability by comparing %BF estimates from the two BP units using predicted TGV. The agreement in %BF estimates between the two BP units, in terms of mean difference (0.571.2 %BF), 95% limits of agreements (À1.9-2.9 %BF) and within-subject CV (3.172.2%), was found to be better than that observed by Collins et al (2004), and was similar to that calculated using measured TGV in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations